A Software System for Viewing and Querying Automatically Generated Topic Maps in the E-learning Domain - Stanescu, L.; Mihai, G.; Burdescu, D.D.; Brezovan, M.; Spahiu, C.S. (Informatica)
A Software System for Viewing and Querying Automatically Generated Topic Maps in the E-learning Domain